Jacques Monod, François Jacob, and the Lysenko affair: boundary work - Marks, John (Johns Hopkins University Press, 2012)
This article looks at the highly influential scientific work of François Jacob and Jacques Monod in the context of the Lysenko affair. It argues that Lysenkoism provided a stimulus to understand and interpret the science they were doing in the field of molecular biology in a particular way, leading to a crucial terminological shift from adaptation to induction in 1953. At a time when new geopolitical borders and barriers were being constructed, molecular biology claimed to have identified a rigidly policed border between the genetic material in the cell nucleus and the rest of the cell. Molecular biology was, in this sense, drawn into a form of intellectual Cold War.